Analisis Fraud Pentagon Dalam Mendeteksi Financial Statement Fraud - Murnandes, Mutia; Budyastuti, Triyani (Universitas Gorontalo, 2025)
The aim of this research is to analyze fraud pentagon on detecting financial statement fraud of BUMN companies listed in Indonesia Stock Exchange for the period 2018-2022. The independent variable used in this study is the fraud pentagon with five factors which consists of pressure, opportunity, capability, rationalization, and arrogance. The dependent variable used in this research is financial statement fraud. The population of this research is BUMN companies for the period 2018-2022. The samples collected used the purposive sampling method. A total of 95 data were selected as a sample. The analysis method for this research uses multiple linear regression. The results shows that pressure and arrogance have a positive effect on financial statement fraud. While opportunity, capability, and rationalization have no effect on the financial statement fraud.